G-CSF and G-CSFR Modulate CD4 and CD8 T Cell Responses to Promote Colon Tumor Growth and Are Potential Therapeutic Targets - Karagiannidis, Ioannis; Jerman, Stephanie J.; Jacenik, Damian; Phinney, Brandon B.; Yao, Ruoxin; Prossnitz, Eric R.; Beswick, Ellen J. (Frontiers in Immunology, 2020)
Cytokines are known to shape the tumor microenvironment and although progress has been made in understanding their role in carcinogenesis, much remains to learn regarding their role in tumor growth and progression. We have identified granulocyte colony-stimulating factor (G-CSF) as one such cytokine, showing that G-CSF is linked with metastasis in human gastrointestinal tumors and that neutralizing G-CSF in a mouse model of colitis-associated cancer is protective. Here, we set out to identify the role of G-CSF and its receptor, G-CSFR, in T cell responses in the tumor microenvironment. We established that in G-CSFR-/- mice, colon tumor growth is significantly decreased. T cell phenotype and cytokine production were also altered. Both in vitro and in vivo approaches revealed that G-CSF/G-CSFR stimulate IL-10-producing, FoxP3-expressing T cells, whereas G-CSFR-/- T cells exhibit increased IFNγ and IL-17A production. Adoptive transfer of G-CSFR-/- CD4+ or CD8+ T cells into tumors increased cytotoxic activity and decreased tumor growth compared to wildtype T cells. Furthermore, peritumoral injection of recombinant IFNγ or IL-17A inhibited colon and pancreas tumor growth and increased expression of cytotoxic factors compared to controls. Taken together, our data reveal an unknown mechanism by which G-CSF, through its receptor G-CSFR, promotes an inhibitory Treg phenotype that limits tumor immune responses. These results furthermore suggest that targeting this cytokine/receptor axis could represent a novel therapeutic approach for gastrointestinal, and likely other tumors with high expression of these factors.